Analyzing kinetics of deformation of boundary rocks of mine workings - Nehrii, S; Sakhno, S; Sakhno, I; Nehrii, T (National Mining University, 2018)
Purpose is to analyze nature of rock deformation and to estimate experimentally state of mine workings being supported under the conditions of areas disturbed by coal mining. Methods. The studies involved field instrumental observations within measuring points equipped with contour benchmarks. Express method was applied to determine height and width of the mine working; typical supported areas were designed; and photographs were taken. The research was conducted in a belt roadway and ventilation raise of western longwall 11 (c18 seam of MM “Pivdennodonbaske No. 1”), and in their connections with the longwall. Findings. It has been determined that the longwall effect in the mine working, being supported repeatedly, is 80 – 60 m in front of a stope; vertical convergence within the area is more than 1 m; floor rise share is almost 76%; and share rate is more than 3 mm/day. It has been specified that local destruction of anchor fitting as well as almost 70% of deformation of frame support is observed within the zone of the longwall affect. It has been identified that potential inrush area from the belt roadway is between supports 3 and 9 of a face zone support; i.e. distance from the seam edge is more than 2.4 m. It has been proved that the use of rigid protective structures is not efficient in the context of soft floor rocks since the protective structures function like dies. Condition of the belt roadway, being constructed and supported behind the longwall, is satisfactory; boundary deformations are within the range of the support flexibility. Originality. Regularities concerning deformation of boundaries of mine workings under the conditions of unstable wall rocks of c18 seam (MM “Pivdennodonbaske No. 1”), when the mine workings are being constructed and supported behind a stope to be used repeatedly for following longwall, have been determined. Regularities of the process when rocks are forced out into a mine working cavity remained after protective structure, being constructed along a mine working at the boundary of the worked-out area, have been identified as well as regularities of vertical convergence rocks within terminal sites of the longwall. Practical implications. The findings can be used to develop measures and means for the stability of development mine workings under the conditions of unstable wall rocks and measures to prevent their fall within the tail longwall sites.

Мета. Аналіз характеру деформування гірських порід та експериментальна оцінка стану гірничих виробок, що підтримуються в зоні впливу очисних робіт із виймання вугілля. Методика. Дослідження проведено методом натурних інструментальних спостережень на вимірних станціях, обладнаних контурними реперами. Проведені виміри висоти і ширини виробки експрес-методом, в характерних ділянках підтримання накреслено ескізи та зроблено світлини. Дослідження проведено в конвеєрній і вентиляційній виробках 11-ої західної лави пласта с18 ДП “Шахтоуправління “Південнодонбаське №1” та їх сполученнях з лавою. Результати. Встановлено, що зона впливу лави у виробці, що підтримується, повторно становить 80 – 60 м перед вибоєм, вертикальна конвергенція в цій зоні більше 1 м, доля підняття підошви близько 76%, швидкість зсувів більше 3 мм/добу. Виявлено, що в зоні впливу лави спостерігається локальне руйнування анкерної фурнітури та близько 70% деформування елементів рамного кріплення. На кінцевій ділянці лави з боку конвеєрної виробки встановлено, що ймовірна область вивалів порід знаходиться між 3-ою та 9-ою стійками привибійного кріплення, тобто на відстані від кромки пласта більше, ніж 2.4 м. Доведено, що застосування жорстких охоронних споруд в умовах слабких порід підошви без додаткових заходів неефективне, оскільки охоронні конструкції працюють як штампи. Стан конвеєрної виробки, що проводиться та підтримується за лавою, задовільний, деформації контуру знаходяться в межах піддатливості кріплення. Наукова новизна. Встановлені закономірності деформування контуру гірничих виробок в умовах нестійких бічних порід пласта с18 ДП “Шахтоуправління “Південнодонбаське №1”, що проводяться та підтримуються позаду очисного вибою та в подальшому використовується повторно для наступної лави. Встановлені закономірності видавлювання порід у порожнину виробки з-під охоронних конструкцій, що споруджуються уздовж виробки на межі з виробленим простором та закономірності вертикальної конвергенції порід на кінцевих ділянках лави. Практичне значення. Використання результатів дослідження є основою для розробки способів та засобів забезпечення стійкості підготовчих виробок в умовах нестійких бічних порід, а також засобів запобігання їх обваленням на кінцевих ділянках лав.

Цель. Анализ характера деформирования горных пород и экспериментальная оценка состояния горных выработок, поддерживаемых в зоне влияния очистных работ по выемке угля. Методика. Исследование проведено методом натурных инструментальных наблюдений на измерительных станциях, оборудованных контурными реперами. Проведены измерения высоты и ширины выработки экспресс-методом, в характерных участках поддержания начерчены эскизы и сделаны фотографии. Исследование проведено в конвейерной и вентиляционной выработках 11 западной лавы пласта с18 ГП “Шахтоуправление “Южнодонбасское №1” и их сопряжениях с лавой. Результаты. Установлено, что зона влияния лавы в выработке, поддерживаемой повторно, составляет 80 – 60 м перед забоем, вертикальная конвергенция в этой зоне более 1 м, доля поднятия подошвы около 76%, скорость смещений более 3 мм/сутки. Выявлено, что в зоне влияния лавы наблюдается локальное разрушение анкерной фурнитуры и около 70% деформации элементов рамного крепления. На конечном участке лавы со стороны конвейерной выработки установлено, что вероятная область вывалов пород находится между 3-й и 9-й стойками призабойной крепи, то есть на расстоянии от кромки пласта больше, чем 2.4 м. Доказано, что применение жестких охранных сооружений в условиях слабых пород почвы без дополнительных мер неэффективно, поскольку охранные конструкции работают как штампы. Состояние конвейерной выработки, проводимой и поддерживаемой за лавой, удовлетворительное, деформации контура находятся в пределах податливости крепи. Научная новизна. Установлены закономерности деформирования контура горных выработок в условиях неустойчивых боковых пород пласта с18 ГП “Шахтоуправление “Южнодонбасское №1”, проводимых и поддерживаемых позади очистного забоя и в повторно используемых для последующей лавы. Установлены закономерности выдавливания пород в полость выработки из-под охранных конструкций, сооружаемых вдоль выработки на границе с выработанным пространством и закономерности вертикальной конвергенции пород на концевых участках лавы. Практическое значение. Использование результатов исследования является основой для разработки способов и средств обеспечения устойчивости подготовительных выработок в условиях неустойчивых боковых пород, а также средств предотвращения их обрушения на концевых участках лав.
Keywords: stability of mine workings; rock mass; deformations; supports; convergence